Association Analysis of a Microsatellite Repeat in the TRIB1 Gene With Prostate Cancer Risk, Aggressiveness and Survival - Moya, Leire; Lai, John; Hoffman, Andrea; Srinivasan, Srilakshmi; Panchadsaram, Janaththani; Chambers, Suzanne; Clements, Judith A.; Batra, Jyotsna, Australian Prostate Cancer BioResource; Yeadon, T.; Saunders, P.; Eckert, A.; et al. (Frontiers in Genetics, 2018)
With an estimated 1.1 million men worldwide diagnosed with prostate cancer yearly, effective and more specific biomarkers for early diagnosis could lead to better treatments. As such, novel genetic markers are sought for this purpose. The tribbles homologue 1 gene (TRIB1) has recently shown to have a role in prostate tumorigenesis and oncomine data-mining confirmed clinical significance of TRIB1 in prostate cancer. For the first time, a polymorphic microsatellite in this gene has been studied for its potential association with prostate cancer risk and aggressiveness. Genomic DNA was extracted from a cohort of 1,152 prostate cancer patients and 1,196 cancer-free controls and the TTTTG-TRIB1 microsatellite was genotyped. The socio-demographic and clinical characteristics were analysed using the non-parametric t-test and two-way ANOVA. Association of the TTTTG-TRIB1 microsatellite and prostate cancer risk and aggressiveness were analysed by binary logistic regression and confirmed by bootstrapping. Total and prostate cancer specific mortality was analysed using the Kaplan Meier test. Genotype and allele correlation with TRIB1 mRNA levels was analysed using the non-parametric Kolmogorov-Smirnov test. To predict the effect that the TTTTG-TRIB1 polymorphisms had on the mRNA structure, the in silico RNA folding predictor tool, mfold, was used. Oncomine data confirmed a significant over-expression of TRIB1 in prostate cancer compared to other cancer types, and an over-expression in prostate cancerous tissue compared to adjacent benign. Three alleles (three to five repeats) were observed for TTTTG-TRIB1. The three-repeat allele was associated with prostate cancer risk at the allele (OR = 1.16; P = 0.044) and genotype levels (OR = 1.70; P = 0.006) and this effect was age-independent. The four-repeat allele was significantly associated with an increase in TRIB1 expression in tumors when compared to adjacent cancer-free tissue. In silico analysis suggested that the TTTTG-TRIB1 alleles may alter TRIB1 mRNA structure. In summary, the three-repeat allele was significantly associated with prostate cancer risk, suggesting a biomarker potential for this microsatellite to predict prostate cancer. Further studies are needed to elucidate the functional role of this microsatellite in regulating TRIB1 expression, perhaps by affecting the TRIB1 mRNA structure and stability.